The incidence rate of Asymptomatic Bacteriuria among LIMU students - Alfurjani, Abdulsalam (faculty of applied basic medical science - Libyan international medical university, 2022)
Symptomatic and asymptomatic bacteriuria is common in pregnant women. A history of previous urinary tract infections and low socioeconomic status are risk factors for bacteriuria in pregnancy. Escherichia coli is the most common aetiologic agent in both symptomatic and asymptomatic infection and quantitative culture is the gold standard for diagnosis. Bacteriuria, which is the presence of bacteria in the urine, is linked to both asymptomatic and symptomatic urinary tract infections, or. It has a significant impact on how microorganisms colonize the urinary system. What's intriguing, though, is the distinction between the microbiological spectrum of various microorganisms infecting different genders, as well as the prevalence of asymptomatic bacteriuria, between the male and female genders.
Keywords: Bacteriuria